ANALISIS PERUBAHAN INTERAKSI SOSIAL DALAM BENTUK KERJASAMA MASYARAKAT KAWASAN SUNGAI KAPUAS (WATERFRONT CITY) - Gusti Nuzurhan; Izhar Salim; Iwan Ramadhan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstract The title of the research is "Analysis of changes in social interaction in the form of community cooperation in the Kapuas River Benua Melayu Laut area, South Pontianak District". The research method used is descriptive method, with a qualitative research form. The source of the data for this research is the people who live in the Waterfront City, Benua Melayu Laut, South Pontianak District. Data collection techniques through interviews, observation and documentation, the data collection tools are observation guides, interview guides and documentation tools. The analysis in this study is presented in a qualitative descriptive manner, using 5 informants. The results of his research that (1) Social interaction in the form of harmony in the Waterfront City area of Benua Melayu Laut Subdistrict of South Pontianak has changed after the existence of the Waterfront City area. With the construction of the Waterfront City area, the behavior of mutual help and tolerance is better in this area. (2) Social interaction in the form of bargaining among the people of the Waterfront City Benua Melayu Laut area, South Pontianak District, has changed since the existence of the Waterfront City area. With many offerings of goods and services in this area which became the economic source of the local community after the existence of the Waterfront City area. Keywords: Social Change, Social Interaction, Waterfront City.